KEARIFAN LOKAL MASYARAKAT TALANG MAMAK DALAM BERLADANG (Jurnal Kajian Lingkungan, 2014)
Talang Mamak is one of Indonesian native tribes residing in IndragiriHulu Riau Province, the total of population is estimated to Â± 3341patriarch or Â±9418 people, spread over five (5) sub districts such as: Rakit Kulim sub district,Batang Gansal sub district, batang Cenaku sub district, Rengat barat sub district,Seberida sub district. Talang Mamak community has some local wisdom infarming ranging from land clearing of the fields to post harvest handling. Theaims of this research is 1) To determine the forms of local wisdom of TalangMamak communities performed in farming 2) Analyzing the meaning of localwisdom in maintaining environmental ecosystems. Farming is a source of foodsecurity in sustaining economics life of Talang Mamak community. Each processof farming activity has the value of wisdom that can be of ancestors forgenerations. The method used was a survey method with a qualitative approachsuch as collecting data through observation, documentation and interviewsdirectly to Patih, batin, custom leaders and farming communities. Determinationof informants or key figures done on purpose by the researcher.The results of the research are 1) The equipment used in farming is veryconventional, 2) Shifting cultivation is a concept in preserving ecosystems, 3) Thestages of farming have good local wisdom as conservation, disaster mitigation andsustainable development.Keywords: Local Wisdom, Farm, Patih, Batin,environmental preservation.